Implementasi Program Pembelajaran Keterampilan Vokasional Massage Bagi Peserta Didik Tunanetra - Hidayat, Samsul; Astuti , Eka Yuli (Papanda Publisher, 2025)
The implementation of vocational massage skills learning program for phase C blind students at SLB Bina Harapan Pangandaran is an educational service strategy aimed at supporting independence and work readiness of blind students. This study aims to describe the process of implementing massage skills programs, identify obstacles faced by teachers, and analyze strategies used to overcome these constraints. The research uses a descriptive qualitative approach with data collection techniques including observation, in-depth interviews, and documentation. The research subjects were massage skills teachers and phase C blind students. The results showed that the program was implemented in stages, starting from basic theory to direct practice with a multisensory approach adapted to the characteristics of blind students. The main obstacles include limited tactile teaching media, unavailability of braille modules, limited practice space, and variations in student abilities. Teachers overcome these obstacles by modifying teaching aids, implementing individual approaches, delivering material orally and through direct demonstration, and involving parents in supporting practice at home. The massage skills program has a positive impact on improving fine motor skills, self-confidence, communication skills, and independence of blind students. The conclusion of this research is that the massage skills program has a positive effect on independence and work readiness of blind students. Research recommendations include developing more varied tactile teaching media, preparing braille and audio modules, improving teacher training, strengthening collaboration with parents and professionals, and providing adequate practice spaces.